2018
DOI: 10.1016/j.ijcard.2017.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two behavioral cardiac rehabilitation interventions on physical activity: A randomized controlled trial

Abstract: Adding three pedometer-based, face-to-face group PA counseling sessions to standard CR increased daily step count and time in prolonged MVPA. The latter persisted at 18months. A telephonic after-care program did not improve PA or SB. Although after-care should be optimized to improve long-term adherence, face-to-face group counseling with objective PA feedback should be added to standard CR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(83 citation statements)
references
References 46 publications
(53 reference statements)
1
81
0
Order By: Relevance
“…According to a previous study, CR could improve cardiac function and activity tolerance of patients which contributed to better prognosis and HRQoL [37]. In this study, the HRQoL of the patients who participated in CR was significantly higher than those who did not.…”
Section: Discussionmentioning
confidence: 45%
“…According to a previous study, CR could improve cardiac function and activity tolerance of patients which contributed to better prognosis and HRQoL [37]. In this study, the HRQoL of the patients who participated in CR was significantly higher than those who did not.…”
Section: Discussionmentioning
confidence: 45%
“…In addition, these types of therapeutic approaches play a major role in resuming everyday work and life in such patients. 9 Parmanto and Saptono 10 reported that 150 minutes of walking per week was enough to achieve health objectives, but Tudor-Locke et al stated that walking 100 steps per minute was an activity of moderate intensity and walking 3000 steps per week could have cardiovascular benefits. 11 Currently, it is not clear whether exercise approaches that include conventional programs (PA recommendations without a pedometer feedback) or pedometer-based programs will have benefits for MI patients.…”
mentioning
confidence: 99%
“…In our study, REVASC patients improved daily steps more than those with pulmonary diseases. A huge variability has been reported in changes in physical activity after pulmonary rehabilitation [33,34]. Considering the overall results, given the high variability of the improvement in daily steps, both in pulmonary and cardiac diseases, we think that a better behavioral approach aimed at improving lifestyles and reducing sedentary behavior in chronic patients should be implemented and added to the training program.…”
Section: Discussionmentioning
confidence: 99%